DESCRIPTIVE ANALYSIS OF GEOLOGICAL SCIENCE FROM THE PERSPECTIVE OF HISTORY - Norinov Fakhriyor Kurbonovich (American Journals, 2023)
By the end of the last century, the introduction of systematic thinking into the theory of geology initiated a new phase of important changes in this field. Theory of systems, stages of formation of geological matter (substance), application of hierarchical laws, concepts of dynamic, statistical, retrospective and prospective systems ensured the study of geological knowledge in a specific system and the consistency of this study.